PENGARUH IMPLEMENTASI RENCANA PELAKSANAAN PEMBELAJARAN GURU TERHADAP HASIL BELAJAR MEKANISASI PERTANIAN DI SMK KRISTEN TOMBATU: THE IMPACT IMPLEMENTATION OF LESSON PLAN OF THE TEACHER FOR THE RESULT OF LEARNING AGRICULTURAL MECHANIZATION IN SMK KRISTEN TOMBATU - Virga Pangemanan; Robert Munaiseche; Lenie Ratag (GEARBOX: Jurnal Pendidikan Teknik Mesin, 2022)
This research aims for knowing the impact implementation of Lesson Plan of the teacher for the result of learning Agricultural Mechanization in SMK Kristen Tombatu. The research was conducted since February until April 2019. The subject of this research are the subject teacher of the Agricultural Mechanization and the students of ATPH department. The research variable that used is free variable, that is X and Y by using correlation and regression technique data analysis. The calculation result of regression analysis shows the impact between two variable (X and Y) be observed from Y = 0,79 + 0,08 X and correlation r = 0,91 show that Lesson Plan variable that used by the teacher with learning result has the  positive impact. The result of learning that reached by the students can be seen from coefficient determination or r2 = 0,86 or 86 % that shows the result of learning is impacted by the Lesson Plan that used by teacher while its residual is determined by other factors that is not researched in this research.